Identification and Epidemiology of a Rare HoBi‐Like Pestivirus Strain in Bangladesh. Issue 3 (21st March 2014) - Haider, N.; Rahman, M. S.; Khan, S. U.; Mikolon, A.; Gurley, E. S.; Osmani, M. G.; Shanta, I. S.; Paul, S. K.; Macfarlane‐Berry, L.; Islam, A.; Desmond, J.; Epstein, J. H.; et al.
Summary The genus pestivirus of the family flaviviridae consists of four recognized species: bovine viral diarrhoea virus 1 (BVDV‐1), bovine viral diarrhoea virus 2 (BVDV‐2), classical swine fever virus and border disease virus. A new putative pestivirus species tentatively named as either 'HoBi‐like pestivirus' or BVDV‐3 has recently been identified in Brazil, Italy and Thailand. Despite reports of serological evidence of BVDV in Bangladesh, the types of the virus circulating in cattle have not been identified. We conducted surveillance in cattle from May 2009 to August 2010 in three government veterinary hospitals to characterize BVDV in cattle of Bangladesh. We tested serum for BVDV using an antigen‐capture ELISA. Of 638 cattle samples, 3% (16/638) tested positive for BVDV antigen. The ELISA‐positive samples were selected for further molecular detection and characterization of BVDV. Molecular analysis of the partial 5′ untranslated region (UTR) nucleotide sequences of BVDV‐positive samples identified the rare HoBi‐like pestivirus or BVDV‐3 virus circulating in cattle of Bangladesh. The identification of this rare HoBi‐like pestivirus or BVDV‐3 strain in Bangladesh warrants further surveillance to evaluate its impact on livestock production.